Pengembangan Media Video Matif (Matematika Interaktif) pada Materi Pecahan Senilai Kelas IV SD Muhammadiyah Gresik - Defianti Fitrotin Nisa’; Arissona Dia Indah Sari; Iqnatia Alfiansyah (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aimed to develop Matif (Interactive Mathematics) video media on the topic of equivalent fractions for fourth-grade elementary school students and to determine its validity, effectiveness, and student responses. The research employed a Research and Development (R&D) method using the ADDIE model. It was conducted at SD Muhammadiyah Gresik during the first semester, involving 19 fourth-grade students. Data collection techniques included interviews, expert validation sheets for content and media, learning effectiveness tests, and student response questionnaires. The development process followed five ADDIE stages. (1) Analysis involved curriculum analysis, needs analysis, and student characteristics analysis. (2) Design focused on creating the learning flow and storyboard. (3) Development produced the video media, which was validated by experts. The material expert validation score reached 97.5%, and the media expert validation score was 91.6%, both categorized as very valid. These results indicate that the material is highly appropriate, clear, and easy to understand, while the media demonstrates excellent quality in visual, audio, typography, language, and usability aspects. (4) Implementation involved testing the media on students, with an N-Gain score of 0.8405, categorized as high, indicating that the media effectively improves students’ understanding. (5) Evaluation was conducted through student response questionnaires, resulting in a score of 95.5%, categorized as very good, showing that students found the media engaging, easy to use, and helpful. Overall, the Matif video media meets the criteria of validity and effectiveness, making it suitable as an innovative learning alternative, with potential for further development through enhanced animations and varied exercises.